Effect of feed Supplemented with Xylam Enzyme on Performance, Carcass Characteristics and Meat Quality of Broiler Chicks - Abdelbasit B. Habib (Egyptian Society for Animal Management, 2016)
This experiment was carried out to identify the impact of inclusion different levels of commercial xylam enzyme (zero, 0.5kg, 0.75kg, and 1 kg) in the feed on performance, carcass characteristics and meat quality of broiler chicks.300 unsexed one- day old (Ross 308) broiler chicks were used in the experiment. The chicks were randomly distributed to four dietary treatments and with each carrying 75 experimental birds. The treatments were subdivided into three replicates; each was given 25 experimental birds. All chicks were fed experimental diets to for five weeks which formulated according to (NRC) to meet the nutrient requirements. The results indicated that addition of xylam enzyme to diet improved significantly (p<0.05) the feed intake, body weight gain and feed conversion ratio values of broiler chicks throughout the experimental period. The results indicated that there were no significant differences between all treatment groups in percentages of commercial carcass cuts (breast, drumstick ,thigh and wing) and chemical composition of breast meat (moisture, fat, and ash), results also showed that no significant differences observed between all treatment groups in some physical properties of broiler breast meat (PH and WHC). It is concluded that adding (1 kg) of commercial xylam enzyme in broiler chicks diets resulted in economic benefits.